Influence of organic enrichment and foliar feeding of nitrogen on productivity, nitrogen uptake of winter drilled fennel (Foeniculum vulgare) (Indian Journal of Arid Horticulture, 2013)
Fennel one of the most important seed spices crop treatment was applied at the time of land preparation and  in India grown mainly as transplanted crop, although it can soil application of nitrogen was done as fertigation in 6  also be raised profitably as a winter direct-seeded crop splits at 15 days interval starting from sowingl. Foliar spray  (Mehta et al., 1990). Direct seeded fennel is very popular of nitrogen was done through urea in 3 splits during  due to short duration than transplanted crop. Thus, direct- reproductive stage at 10 days interval as per treatment. The  th seeded fennel is profitable than other winter crops like fennel variety RF 101 was sown on 11 November using 10  th mustard chickpea and wheat (Mehta et al., 1990). Fennel kg seed/ha and harvesting in 4 week of April in both the  being a wide rowed crop can be grown successfully under years. The crop was sown in paired row spacing of 30 cm x  drip in water scarce state like Rajasthan and various 60 cm i.e. 30 cm between rows in a pair and 60 cm between  experiments conducted at Swami Keshwanand Rajasthan two pairs in 120 cm drip line spacing to reduce cost of drip  Agricultural University, Bikaner concluded that 80% ETc is system. The crop was raised at drip irrigation level of 80%  optimum level for drip irrigated fennel. Indian agriculture is ETc through out the growing period, which is recommended  facing a serious problem of declining total factor as optimum for the zone. The details of irrigation events and  productivity and low crop response to inputs chiefly monthwise irrigation water applied are presented in table 1.  fertilizers. Declining crop response to water and fertilizer The soil was sandy loam having field capacity 7.2%,  particularly nitrogen is due to deteriorating soil health and permanent wilting point 1.8%, bulk density 1.51 g/cc, pH  productivity. Organic matter enrichment can rejuvenate the (1:2) 8.2, electrical conductivity (1:2) 0.2 dS/m, organic  soil health in a dramatic manner. This will lead to increased carbon 0.11% and available P and K 15 and 320 kg/ha,  efficiency of water and fertilizers particularly nitrogen. respectively.
Keywords: vermicompost; bacteria; nitrogen